In vitro antimicrobial activity of Miswak extracts against some oral pathogenic isolates - Omer, Abdul–Ghany; Qarani, Sozan Muhsin; Khalil, Amera Kamal (Zanco Journal of Medical Sciences (ZJMS), 2010)
Background and objective: Siwak, Miswak, or Arak (Salvadora persica ) belongs to Salvadoraceae and is considered as the most widely used twigs since early times by Babylonians some 7000 years ago, it was later used throughout the Greek and Roman empires, and has also been used by ancient Egyptians and Muslims. The aim of this study was to determine the antibacterial activities of different extracts of Siwak on the growth of different oral isolates of Streptococcus mutans, Staphylococcus aerus and Candida albicans. Methods: Experiments were conducted in the laboratories of the College of Science, University of Salahaddin and College of Dentistry, Hawler Medical University for a period from Jun. 2008 to Feb. 2009, to determine the effects of different Siwak (Salvadora persica) extracts at concentrations of 500, 1000, 5000 and 10000 µg/ ml on the growth of different oral isolates of Streptococcus mutans, Staphylococcus aureus, and Candida albicans. Results: The results showed that all Siwak extracts (especially Siwak aqueous extract) were effective against Streptococcus mutans. and Staphylococcus aureus. The strongest antibacterial activity was observed using the concentrations of 10000 µg/ ml. While Siwak extracts were ineffective against Candida albicans. Conclusion: Siwak extracts had significant antibacterial effect against Streptococcus mutans. and Staphylococcus aureus, and ineffective against Candida albicans.